Burden of stillbirths and associated factors in Yirgalem Hospital, Southern Ethiopia: a facility based cross-sectional study - Sintayehu Mengesha; Mesay Hailu Dangisso (BMC, 2020)
Abstract Background Stillbirth is an adverse pregnancy outcome of public health importance causing considerable psychosocial burden on parents and their family. Studies on stillbirth are scarce in southern Ethiopia. An assessment of stillbirths and associated factors in health care settings helps in devising strategies for tailored interventions. Therefore, we assessed the burden of stillbirths and associated factors in Yirgalem Hospital, southern Ethiopia. Methods A facility based cross-sectional study was conducted between 1 and 2015 and 30 July 2016. We randomly selected medical records of pregnant women from a hospital delivery registry. Bivariate analysis was employed to assess the association between independent and dependent variables using chi-square with significant p-value. Multivariate logistic regression was used to identify independent risk factors for stillbirths and to control for confounding variables. Results Of 374 reviewed records of pregnant women, 370 were included for the study. The magnitude of stillbirths was 92 per 1000 births. Fifteen (44.1%) of fetal deaths occurred after admission to the hospital. In multivariate logistic regression, stillbirths were higher among low birth-weight babies (< 2500grams) (adjusted odds ratio (AOR): 10.70, 95% CI 3.18-35.97) than normal birth-weight babies (2500-<4000). Pregnant women who experienced a prolonged labour for more than 48 hours were 12 times (AOR: 12.15, 95% CI 1.76-84.12) more likely to have stillbirths than pregnant women without a prolonged labour. Pregnant women with obstetric complications were 18.9 times more likely to have stillbirths than pregnant women without obstetric complications. Similarly, pregnant women with at least two pregnancies were more likely to have stillbirths than pregnant women with less than two pregnancies (AOR: 4.39, 95% CI 1.21-15.85). Conclusions We found a high burden of stillbirths in the study setting. Modifiable risk factors contributed to a higher risk of stillbirths; therefore, tailored interventions such as early identification and management of prolonged labour and obstetric complication at each level of health system could avert preventable stillbirths.